(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The article investigates key aspects and issues of investment activity in Ukraine in national and regional dimensions. A detailed analysis is given for the dynamics of capital investments and foreign direct investments in the past decade. Main factors hindering the economic growth, as well as the influence of investment intensity upon the economy, are considered. An econometric analysis is conducted in order to understand the relation between investment activity and GDP growth in Ukraine. Based on results of the analysis a set of necessary measures is given, which are urgently needed in order to improve the economic situation in Ukraine and aid its growth.